The dramatic dimension in the ha'-rhymed poem of Ubayd Allah ibn Qais Al-Raqiyyat. (Journal of Hama University, 2021)
The old Arabic poem is alyrical poem, but we don’t view this lyricism as pure lyricism, Rather, it enters adramatic dimension based on contradiction, so an idea is contrasted with an idea, and an emotion meets an emotion, and because Contrast and conflict, the essence of drama, are two main pillars in the theatrical text. We will study this dimension through correspondence between poetry and theater based on contradiction and conflict, which are the essence of drama. The research deals with a problematic issue for many critics and scholars; namely it corresponds ancient poetry with the theatre, and its association with drama (theatre lifeblood) but this study confirms that there is a dramatic dimension that we find clearly in the poetry of flirtation in the Umayyad era, so the elements of lyricism in it did not stand as a barrier in the way of some dramatic features that were blended into it. The research sheds light on the dramatic dimension in the vexations flirtation that spontanearesly penetrated into it before the term of "drama" erystallizes dramatically, and reaches what is now being mature and complete, to reveal the meanings of conflict that have emerged due to the crises that poets have undergone in the Umayyad period.